Sexual Assault Policies and Consent Definitions: A Nationally Representative Investigation of U.S. Colleges and Universities. (3rd July 2017) - Graham, Laurie M.; Treves-Kagan, Sarah; Magee, Erin P.; DeLong, Stephanie M.; Ashley, Olivia S.; Macy, Rebecca J.; Martin, Sandra L.; Moracco, Kathryn E.; Bowling, J. Michael
ABSTRACT: Campus sexual assault (SA) policies and sexual consent definitions have not been widely studied. The study team conducted a nationally representative review of college and university websites ( n = 995), assessing the prevalence of publicly accessible online policies and definitions and examining associations with school characteristics. A content analysis was performed on a subsample ( n = 100) of consent definitions. Most schools (93.0%) had an SA policy and consent definition (87.6%) available online. Schools were more likely to have a policy or consent definition if they were large (≥5, 000 students), public, or had a female enrollment of ≥33%. Detail and comprehensiveness of definitions varied. Findings highlight opportunities for schools—especially small schools, private schools, and those with more male students—to increase access to SA policies and consent definitions.